The Correlation Analysis Between Self-Care and Life Quality of Congestive Heart Failure Patients - Putri, Arsalna Daersa; Rizkifani, Shoma; Nurbaeti, Siti Nani (Media Karya Kesehatan, 2023)
Congestive heart failure (CHF) is a failure of the heart to transport blood and oxygen throughout the body caused by abnormalities in the heart's function and structure. CHF patients will experience obstacles in their daily routine activities, which can affect the patient's self-care. Self-care is the ability or behavior of a person to manage himself. Self-care will affect the quality of life of a patient with CHF. Quality of life is a person's ability to perform activities according to the outlook of his role in everyday life. The aim of this study is to analyze the relationship of self-care with the quality of life of CHF patients in heart polyclinic RSUD dr. Soedarso. The research method used in this case is cross sectional with correlation design. The samples were taken using purposive sampling with a total sample of 83 patients. The inclusion criteria for this study is patients suffering from CHF disease (more than 1 month), patients who can read, write, communicate well with the researchers, patients over 18 years of age, and patients who are willing to fill in informed consent, questionnaires/interviews. The results of the study showed that the self-care of patients was in the good range of 56 patients (67,5%) and 27 patients (32,5%) were in the poor range. The quality of life of patients is also in the high range of 57 patients (68.7%) and low range of 26 patients (31.3%). The data analysis using the spearman rank correlation test resulted in a p value of 0.001 (<0.05) and a correlation coefficient of (r)=0.363. The conclusion of the study is that there is a positive correlation between self-care and the quality of life of CHF patients in heart polyclinic RSUD dr. Soedarso. Keywords: Congestive heart failure, selfcare, quality of life.